Understanding the effect of university service quality on student loyalty to online learning adoption in the light of COVID-19 pandemic / Ado Ismail Sabo - Sabo, Ado Ismail (Faculty of Information Management, 2022)
The COVID-19 pandemic has caused significant disruption to a wide range of human activities, with academic commitment at universities being one of the most important. By the end of COVID-19, everyone will recognise that universities cannot be held responsible for the adoption of online studies. However, in the context of the COVID-19 pandemic, it is critical to investigate the relationship between "University Service Quality" and "Student Loyalty" in order to better comprehend the impact of online learning adoption. Studying the Influence of university service quality on student loyalty to online learning adoption in the context of the COVID-19 pandemic, on the other hand, will lead to greater understanding of how students' commitment to online learning is linked to how satisfied they are with their university's services in the wake of the COVID-19 outbreak. As a result, a focus group experiment was conducted with university students to determine their level of loyalty towards their universities based on their online studies instead of face-to-face. According to the findings, students believe they should be compensated in some way because they paid for face-toface instruction while receiving online instruction. The universities should not charge the same amount for online learning as it does for face-to-face study. Consequently, they lost a lot of faith in the university, and their loyalty to the university dropped drastically.